Chicken Embryo as Model for Effects of Nnitrosodimethylamine Using Morphology, Haematology and Proteomic Analyses During Embryogenesis - Sulaiman, Mohd Rosni (2009)
This study was carried out to investigate the developmental toxicity effects of an established carcinogen namely N-Nitrosodimethylamine (NDMA) and its administration method on the early and mid embryogenesis of chicken. The study was also conducted to test the suitability of chicken embryo in its early and mid embryogenesis stages as a model for developmental toxicity test. Fertilized eggs were divided into three groups (control (untreated), control vehicle and NDMAtreated) with six eggs in each group and incubated at 37.5ºC for 11 different incubation times. Several methods and techniques were modified, optimized and developed prior to be used in the analyses. The effect of NDMA was assessed based on gross morphological (early and mid embryogenesis), haematological (only in mid embryogenesis) and proteomic (early embryogenesis) analyses of the developing chicken embryos. The newly developed method and technique, i.e., Adobe Photoshop gross morphological measurement method and isoelectric focusing (IEF) tube gel labeling technique were optimized and applied throughout this study. The normal development and growth of the chicken embryos in the early and mid embryogenesis were found to be severely affected by NDMA as indicated by gross morphological and haematological data. Malformations in the development of embryos and failure of peripheral blood vessels formation (angiogenesis) in their yolk sac were visibly apparent for NDMA-treated group. The administration method of NDMA did not affect the normal chicken embryos early and mid embryogenesis as there were no significant (p>0.05) difference between control and control vehicle groups in all of the gross morphological and haematological parameters tested. Around 100 to 180 protein spots were resolved on the 2DE gels in the control, control vehicle and NDMA-treated groups. A total of six most remarkably expressed protein out of 51 identified proteins were found to be directly or indirectly involved in NDMA possible angiogenesis inhibition and/or hematotoxic effect in the early chicken embryogenesis. These six proteins were identified as PIT54, VEGF-D, ApoA1, unnamed protein product of IgY, TBP-like protein 1 and Kelch-like protein 7, respectively. The PIT54, VEGF-D, and ApoA1 proteins seemed to be directly affected by the NDMA metabolite (s) or by its (their) angiogenesis inhibition effect. The unnamed protein product of IgY, TBP-like protein 1 and Kelch-like protein 7 which seemed to be indirectly affected by NDMA, were closely interrelated with each other and simultaneously upregulated only in the control group at 72 and 96 hours of incubation. At the proteome level, the in ovo administration method of NDMA seemed to affect the embryos by suppressing their normal responses to the possibly adverse IgY-antigens interaction. This as indicated by the downregulation of the unnamed protein product of IgY and its interrelated proteins (TBP-like protein 1 and Kelch-like protein 7) in the control vehicle group of embryos. It is uncertain whether this effect is harmful or not to the general chicken embryo development and growth since the gross morphological and haematological results showed no observable effect of this administration method. However, any disturbance to the normal cellular response should be taken into a serious consideration. In conclusion, NDMA in its normal carcinogenic dosage could potentially cause developmental toxicity in the early and mid embryogenesis of chicken through its possible primary role as an angiogenesis inhibitor and/or secondary role as a hematotoxicant. The in ovo administration method of NDMA using sterile dionized water is evident not to adversely affect the normal physical development and growth of the embryos in their early and mid embryogenesis. However, it seemed to affect the expression of certain proteins at proteome level. Therefore, it is a must for any future study involving this in ovo administration method to also include the control vehicle in their experimental designs to avoid false positive results that might arise from the administration method itself. It is also evident from this study that chicken embryo in its early and mid embryogenesis stages is a suitable model for developmental toxicity test.